Developing Students’ Sheets for Transaction Recording Materials into Special Journal of Trading Company - Pattashiki, Vidia; Leksono, Ibut Priono; Cholid, Abd. (International Journal of Educational Technology and Learning, 2019)
In line with the implementation of the 2013 curriculum, as it was promised by the government that teaching materials relating to student books and teacher handbooks should be provided. However, there are no such things available yet as promised. This creates difficulties for students in learning activities and teachers in teaching activities. Therefore, the purpose of this development is to produce the final product in the form of student’s activity sheet (lembar kegiatan siswa/LKS) as learning support for trading company accounting practice material on basic competencies applying transaction records into specialized trading company journals, analyzing the feasibility of worksheets, and analyzing student responses to LKS developed using types of research and development. A model introduced by Moelenda, ADDIE (Analysis, Design, Development, Implementation, and Evaluation), was applied. The results showed a content feasibility score of 89.36% with very feasible criteria, the feasibility of presentation was 89.84% with very feasible criteria, language feasibility of 84.54% with very feasible criteria, and graphic eligibility of 86.66% with fair criteria. The average four components of the study and validation are 87.6% with very feasible criteria. While the average score of the percentage of student responses is 83% with very good criteria. So that it can be concluded that the developed worksheet is stated to be very feasible to use in the learning process and obtain a positive response from students.